2010
DOI: 10.1080/09593330.2010.484076
|View full text |Cite
|
Sign up to set email alerts
|

The genusThermotoga: recent developments

Abstract: The genus Thermotoga comprises extremely thermophilic (Topt ≥ 70°C) and hyperthermophilic (Topt ≥ 80°C) bacteria that have been extensively studied for insights into the basis for life at elevated temperatures and for biotechnological opportunities (e.g., biohydrogen production, biocatalysis). Over the past decade, genome sequences have become available for a number of Thermotoga species, leading to functional genomics efforts to understand growth physiology as well as genomics-based identification and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 97 publications
2
18
0
Order By: Relevance
“…It has been shown that MRE11 can be associated with RAD50 to actively bind DNA. This complex forms a catalytic head that contains an ATP-stimulated nuclease and DNA binding activity that indicates its potential role in processing DNA double-stranded breaks in T. maritima (2,30,32,33). It was also found here that a minimum of 100 nt was required for recombination and that a putative recombinogenic sequence (AGCGG) located at the 3= end of pyrE and upstream region of pyrE may play a role in recombination at that locus.…”
Section: Discussionsupporting
confidence: 57%
“…It has been shown that MRE11 can be associated with RAD50 to actively bind DNA. This complex forms a catalytic head that contains an ATP-stimulated nuclease and DNA binding activity that indicates its potential role in processing DNA double-stranded breaks in T. maritima (2,30,32,33). It was also found here that a minimum of 100 nt was required for recombination and that a putative recombinogenic sequence (AGCGG) located at the 3= end of pyrE and upstream region of pyrE may play a role in recombination at that locus.…”
Section: Discussionsupporting
confidence: 57%
“…The 10 Thermotoga species currently identified can clearly be divided into one group with optimum growth temperatures of 65 to 70°C and another group with optimum growth temperatures of 75 to 80°C (Table 1). 16S rRNA sequences indicate that the isolates with higher optimum growth temperatures are more closely related (Ն99% identical) to each other than to the less thermophilic Thermotoga strains (15). Complete genome sequences are available for seven Thermotoga species, and all of these, except for T. lettingae and T. thermarum, belong to the group of higher-temperature species (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…maritima, over 70 bacterial species belonging to this phylum have been isolated from a variety of geothermal or volcanically heated environments including oil reservoirs, hydrothermal vents, terrestrial hot springs, etc. (Patel et al 1985;Antoine et al 1997;Reysenbach 2001;Alain et al 2002;Balk et al 2002;Urios et al 2004;Huber and Hannig 2006;Dipippo et al 2009;Frock et al 2010). Recently, the presence of bacteria related to the Thermotogales has also been reported in mesophilic, low temperature environments (Nesbo et al 2010).…”
Section: Introductionmentioning
confidence: 97%